Caratteristiche morfodinamiche di due rock glaciers attivi nel gruppo Adamello Presanella - SEPPI R; BARONI C. BASSI L.; CARTON, ALBERTO (2006)
Morphodynamic characteristics of two active rock glaciers in the Adamello-Presanella Group - Multitemporal topographic surveys on two rock glaciers in the Adamello-Presanella Group have been carried out. The aim of these surveys was to check the morphometric characteristics of the landforms and to get detailed information about their dynamic behaviour. In order to do this, two rock glaciers located in Val di Genova and Val d’Amola and lying at the upper and lower limit of the belt containing active landforms have been selected. On each rock glacier, a monitoring network of 25 boulders has been established. The measurements carried out show that they are presently in motion and that they moved in three years (2001-2004) with velocities of respectively 0.15 m year-1 and 0.10 m year-1. On both the rock glaciers, different areas characterized by homogeneous displacement rates can be found. In particular, on the rock glacier located at the lower altitude the geomorphologic characteristics of the frontal surface support the dynamic model highlighted by the topographic surveys. In fact, the more dynamic western sector of the frontal area (0.15- 0.18 m year-1) is characterized by an evident swollen lobe and by a steep, unstable and vegetation-free frontal slope. In each monitoring interval (2001-2002 and 2002-2004) the behaviour of the two rock glaciers has been the same. Nevertheless, a general acceleration of the fast-moving boulders has been observed in the second interval (2002-2004).